Elements of microwave networks basics of microwave engineering - Vittoria, C. (World Scientific, 1998)
This text serves as a transition between introductory courses in electromagnetism and rapid advances in microwave technology. Discussions on areas such as lossy and multiple connect are designed to arouse the interest of novice students, enhance analytical skills of practitioners, and invite advanced students to explore novel concepts developed here. Discussions on ferrite networks are presented as an integral part of the author's theoretical methodology. Includes exercises and answers. For use in an undergraduate elective course. Annotation copyrighted by Book News, Inc., Portland, OR
Keywords: Microwave circuits -- Mathematical models.; Microwaves -- Mathematical models.; Microwave transmission lines -- Mathematical models.; elektronické knihy; electronic books